Academic success of mature students in higher education: a Portuguese case study - Santos, Lucília Maria Pessoa Tavares dos (2016)
The increasing number and diversity of non-traditional participants who are now entering Higher Education Institutions (HEI) highlights the relevance of questioning on mature students’ academic success. Thus, the purpose of this study is to characterise mature students over 23 years old (MS23) of two Portuguese HEI, and understand their academic success. The study focuses on results obtained through a case study, based on quantitative and qualitative data: questionnaires and focus groups, respectively. We discuss the influence of different variables (such as: age, gender, area of study, schooling level at the entrance to the university, family monthly income) on MS23’s academic success, and we also describe some obstacles they face and changes they perceive when attending HEI. Results seem to demonstrate a similar tendency between data gathered on both HEI. Some recommendations for HEI, based on the results, are presented in the final section of this article.